A Review on Pharmacological Activity of Monarda fistulosa L. - Wahyudi, Berthalia Marshella; Chung, Cecilia Ashley; Chelovna, Celine; Soetanto, Fenny; Anggasta, Giovanni; Zafira, Qastalia; Maulida, Nurul Fajry; Crystalia, Audrey Amira (Indonesia International Institute for Life Sciences, 2022)
Monarda fistulosa is a plant often used in traditional medication with numerous benefits. This review paper aims to elaborate on the phytochemicals of Monarda fistulosa that contribute to its pharmacological activity. Numerous studies have found the bioactive compounds of Monarda fistulosa including carvacrol, thymol, thymoquinone, flavonoid, ????-pinene, caryophyllene oxide, limonene, and geraniol. Researchers have found several pharmacological activities in relation to these compounds including antimicrobial, antidiabetic, anticancer, anti-inflammatory, antioxidants, and immunomodulatory properties. Evidence shows that Monarda fistulosa has potential for applications in many areas. Nevertheless, further clinical studies still have to be conducted to assess the effects of this plant.